2007
DOI: 10.1016/j.hrthm.2007.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Molecular composition of the intercalated disc in a spontaneous canine animal model of arrhythmogenic right ventricular dysplasia/cardiomyopathy

Abstract: Mutation(s) responsible for ARVD/C in Boxers lead, directly or indirectly, to severe modifications of mechanical and electrical cell-cell interactions. Furthermore, significant reduction in gap junction formation may promote a substrate for malignant ventricular arrhythmias. This model may help to advance our understanding of the molecular basis, pathophysiology, and potential therapeutic approach to patients with ARVD/C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 38 publications
2
69
1
Order By: Relevance
“…79 Inherited ARVC in boxer dogs is associated with the loss of gap junctions, suggesting that, as in humans, disruption of the molecular composition of the intercalated disc is a component of the disease. 80 However, the genetic causes of ARVC in dogs remain unknown, and efforts to identify mutations in desmosomal molecules have been futile. Alternatively, a number of investigators have turned to genetically modified mice as a model to study ARVC pathophysiology.…”
Section: Desmosomal Integrity and Junctional Complexes: Results From mentioning
confidence: 99%
“…79 Inherited ARVC in boxer dogs is associated with the loss of gap junctions, suggesting that, as in humans, disruption of the molecular composition of the intercalated disc is a component of the disease. 80 However, the genetic causes of ARVC in dogs remain unknown, and efforts to identify mutations in desmosomal molecules have been futile. Alternatively, a number of investigators have turned to genetically modified mice as a model to study ARVC pathophysiology.…”
Section: Desmosomal Integrity and Junctional Complexes: Results From mentioning
confidence: 99%
“…In arrhythmogenic right ventricular dysplasia/cardiomyopathy (ARVD/C), decreased Cx43 levels are found already in the early stages, whereas fibrosis becomes more abundant during the progression of the disease. 12,13 This suggests a possible role of reduced Cx43 expression levels in the deposition of collagen in vulnerable hearts. A supportive recent in vitro study 14 suggested increased proliferation of cardiac fibroblasts, the primary source of cells responsible for production of interstitial collagen, once the intercellular communication was inhibited.…”
Section: Clinical Perspective On P 390mentioning
confidence: 98%
“…35 Because plakophilin-2 does not contain a PDZ domain, this suggests that Na v 1.5 could be differentially regulated by multiple proteins at the intercalated discs including SAP97 and plakophilin-2, similarly to the lateral membrane where it interacts with the DMC and ankyrin-G, within complexes that may or may not be distinct (Figure 8). Deciphering the specific and distinct roles of the different proteins in trafficking and/or anchoring of cardiac ion channels including Na v 1.5 to different cellular compartments will be the goal of future experiments.…”
Section: Physiological Relevance Of the Two Regulating Mechanismsmentioning
confidence: 99%